PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SEKOLAH DASAR - Elfiza; Nisa, Sahrun; Suciana, Fadila; Ahmad, Syafri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Critical thinking skills are one of the 6C skills that students need to master in 21st-century learning. Based on interviews with fourth-grade teachers at SDN 11 Indarung and SDN 06 Padang Besi, it was found that mathematics learning had not fully supported the development of students' critical thinking skills. Students lacked initiative in developing their reasoning abilities and tended to be passive during the learning process. One effort that can be made is to implement the Realistic Mathematics Education (RME) approach. This study aimed to determine the effect of the Realistic Mathematics Education (RME) approach on the critical thinking skills of fourth-grade elementary school students. The research method used was quasi-experimental research with a nonequivalent control group design. The independent variable was the Realistic Mathematics Education (RME) approach, while the dependent variable was students' critical thinking skills. The research population consisted of fourth-grade students at SDN 11 Indarung and SDN 06 Padang Besi in the even semester of the 2025/2026 academic year, selected through purposive sampling. The experimental class received treatment using the RME approach, while the control class used conventional learning methods. Data were collected through pretests and posttests using an essay test instrument measuring critical thinking skills. The results showed that the mean pretest scores of the experimental and control classes were 25.20 and 27.50, respectively, while the mean posttest scores were 87.93 and 79.19, respectively. The hypothesis test results showed that tcount > ttable, namely 3.741 > 2.045, indicating that Ha was accepted and H0 was rejected. Therefore, the RME approach had a positive and significant effect on the critical thinking skills of fourth-grade elementary school students.